2014
DOI: 10.1121/1.4863266
|View full text |Cite
|
Sign up to set email alerts
|

The influence of material anisotropy on vibration at onset in a three-dimensional vocal fold model

Abstract: Although vocal folds are known to be anisotropic, the influence of material anisotropy on vocal fold vibration remains largely unknown. Using a linear stability analysis, phonation onset characteristics were investigated in a three-dimensional anisotropic vocal fold model. The results showed that isotropic models had a tendency to vibrate in a swing-like motion, with vibration primarily along the superior-inferior direction. Anterior-posterior (AP) out-of-phase motion was also observed and large vocal fold vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…This study confirmed a previous experimental observation that anisotropic vocal folds were better able to maintain their position against the subglottal pressure (Zhang, 2011(Zhang, , 2014Xuan and Zhang, 2014). Although the vocal folds were still pushed open with increasing subglottal pressure, the increase in the mean glottal area and flow rate decreased with increasing vocal fold AP stiffening (i.e., increasing anisotropy) and were much smaller than those observed in isotropic models.…”
Section: A Summary Of Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…This study confirmed a previous experimental observation that anisotropic vocal folds were better able to maintain their position against the subglottal pressure (Zhang, 2011(Zhang, , 2014Xuan and Zhang, 2014). Although the vocal folds were still pushed open with increasing subglottal pressure, the increase in the mean glottal area and flow rate decreased with increasing vocal fold AP stiffening (i.e., increasing anisotropy) and were much smaller than those observed in isotropic models.…”
Section: A Summary Of Resultssupporting
confidence: 76%
“…The wave-like motion, particularly on the lateral surface, was also more obvious in Fig. 3 with an increased AP stiffness, which is consistent with the observation in Zhang (2014).…”
Section: Model Validationsupporting
confidence: 80%
See 3 more Smart Citations